Sport an agent in intergrating Malaysian society - Omar, Abdul Hafidz; Abdul Majid, Norazman; Puteh, Fatimah (2006)
Malaysia is a multiracial country having three races namely, Malay, Chinese and Indian. Each of these races practices a different religion, customs, rituals, language and belief system. During the colonial occupation and even immediately after Malaysia gained its independence in 1957, there was segregation of the main 3 main races with each race dominating only certain areas of Malaya, the Chinese congregated around the town areas specifically controlling the tin-mines industry, the Malays were seen mostly in the paddy plantation industry while the Indians dominating the rubber plantation industry. These differences are not only seen in their choice of occupation and living areas but even to the extent of their choices of sporting activities. With such differences and diversity in beliefs and practices one would think that it would be difficult for these different races to work together as a team. However, with the introduction of the Malaysian Sport Policy, the different races were able to work together as one big family. This paper will discuss how the elements of sport are able to bring together these three main races to work together as one team and be proud as a nation. The introduction of the Malaysian Sport Policy after the racial riot in May 1969 has successfully installed among the different races elements such as society togetherness, multiracial cooperation and tolerance, friendship and most importantly loyalty to the nation through sport and physical education. Sport is seen not only as a competition but it also acts as a catalyst integrating these three main races of different societal values. The paper provides an insight to how this policy is carried out, the elements stressed upon in the policy and the reported responses of the athletes themselves on the beliefs on how sport has brought them together as a team.